2017
DOI: 10.1017/s0967199417000223
|View full text |Cite
|
Sign up to set email alerts
|

The effect of kinetic heat shock on bovine oocyte maturation and subsequent gene expression of targeted genes

Abstract: The exposure of oocytes to heat stress during the maturation process results in harmful effects to their internal organelles, low fertilization capability and higher embryonic losses. In the present experiment the effect of heat shock (HS) during the maturation process was assessed. In Assay 1, oocytes from winter (December-March; n = 100) and summer (June-September; n = 100) months were collected and matured to analyse their HS tolerance. Total RNA was extracted from matured oocytes and cDNA synthesis was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
(45 reference statements)
0
6
0
Order By: Relevance
“…Several research developed in vivo show cortisol as a stressful hormone, affects bovine metabolism, in general, and reproduction in particular [30][31]. Previously studies showed that in the Azores, fertility of bovine decreases drastically to 35% in the summer period, achieving 78% in the non-hot periods as spring and autumn [44][45]. Several hypotheses have been purposed to explain this shut in the hot periods [18,32,45].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several research developed in vivo show cortisol as a stressful hormone, affects bovine metabolism, in general, and reproduction in particular [30][31]. Previously studies showed that in the Azores, fertility of bovine decreases drastically to 35% in the summer period, achieving 78% in the non-hot periods as spring and autumn [44][45]. Several hypotheses have been purposed to explain this shut in the hot periods [18,32,45].…”
Section: Resultsmentioning
confidence: 99%
“…Previously studies showed that in the Azores, fertility of bovine decreases drastically to 35% in the summer period, achieving 78% in the non-hot periods as spring and autumn [44][45]. Several hypotheses have been purposed to explain this shut in the hot periods [18,32,45]. Heat stress genes, such HASP14 and Cx34 are activated during summer, when outside temperature rises over 25 ºC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Summer‐collected oocytes exhibited lower IVM rates than winter‐collected oocytes. This observation has been associated with HS‐induced downregulation of the HSPA14 gene (Pavani et al, ). Oocytes collected during the summer showed more than 20 times higher incidence of anomalous metaphase II morphology than control oocytes.…”
Section: The Female Reproductive Tractmentioning
confidence: 90%
“…In addition, treatment-specific effects have been observed for IVM oocytes. For example, Kahlon (2016) has shown that exposure to bisphenol A can decrease the total amount of DNMT1 protein in oocytes, whereas prolonged heat shock and melatonin increase transcript amount Pavani et al 2017). Further, work from Van Hoeck et al (2011) identified increased levels of DNMT3A transcript in blastocyst stage embryos that developed from oocytes exposed to nonesterified fatty acids (NEFA) during IVM.…”
Section: The Oocytementioning
confidence: 99%